Human Rights - Toivanen, Reetta; Cambou, Dorothee (2021)
Human rights are among the key concepts of sustainability science because they constitute the basis for sustainable well-being in any given society. Human rights form an understanding of a world in which individuals and peoples can trust in justice and claim rights by virtue of being human. The idea of an international human rights law is that it is not up to a specific government to decide how it treats individuals and peoples living in its territory. Thus, human rights form a discourse of emancipation with a universal outreach. They are essential to achieve sustainable development as specified inthe 2030 Agenda for Sustainable Development, which indicates that the implementation of the Sustainable Development Goals (SDGs) is based on human rights. However, there are some tensions that continue to oppose SDGs to human rights. This is partly the case in relation to the rights of Indigenous peoples, an issue that will be further explicated in this contribution with regard to the situation of the Indigenous Sámi people. This chapter elaborates on the concept of human rights from the perspective of sustainability sciences. It explores human rights as a concept of law and as a concept of global politics, and it analyzes its differing functions depending on the contexts in which it is applied. This contribution considers the recent interconnections of human rights with the issues raised by sustainable development and the rights of Indigenous peoples. Peer reviewed